Efektivitas Efektivitas Model Discovery Learning Terhadap Kemampuan Menulis Resensi Berdasarkan Cerpen Yang Ditulis Oleh Teman Siswa : Efektivitas Model Discovery Learning Terhadap Kemampuan Menulis Resensi Berdasarkan Cerpen Yang Ditulis Oleh Teman Siswa - Marjulita Lita; Upit Yulianti DN; Trisna Helda (Prodi Pendidikan Bahasa dan Sastra Indonesia, Universitas PGRI Ronggolawe, 2024)
This research is motivated by the ability to write reviews based on short stories written by fellow students using the Discovery Learning model with a quantitative research type, the research design used is one group pretest, post test, design. The population in this study were students of the F after using the Discovery Learning model it became 81.16 with Quality in the range of 76-85% good qualifications (B).